Distinguishing skill from technique in football - Bennett, K. J. M.; Fransen, J. (Science and Medicine in Football, 2024)
The current commentary adopts a skill acquisition science perspective on the distinction between skill and technique, two constructs often confused in football science and practice. It first positions technique as a coordination pattern. It then argues that experts rarely (if ever) coordinate their neuromuscular system in the same way through evidence of inter- and intra-individual movement variability from football science and other domains of sport science. It concludes by asserting that skill distinguishes itself from technique by its requirement for functional and beneficial coordination patterns, meaning that coaches, sporting practitioners and researchers should consider skill as any technique that an athlete successfully applies to a situation that requires it.